(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Dependencies between signals and dependence of signals on time are strictly non-linear. Non-linear elements, commonly used in the synthesis of automatic control systems, include: a two-point link, a two-point link with hysteresis, a three-point link, a three-point link with hysteresis, a module, saturation with insensitivity.